1991
DOI: 10.1163/22977953-04801002
|View full text |Cite
|
Sign up to set email alerts
|

Development of simulators in medical education

Abstract: The historical development of simulators is presented in respect to their application in medical training. Simulators allow, to some extent, practical training without any inconvenience for patien ts. The earliest sim ula tors in the history of medicine were the obstetrical manikins introduced toivards 1700 by father and son Grégoire of Paris and primarily intended for the instruction of lay people, i.e. midwives. Their further development is followed up to contemporary models of highly specialized use. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Training for clinical practice, however, is not confined to work on the body of live humans. Indeed, there is a long and significant history of the use of 'simulators' in both medical and dental education -including the use of cadavers and discarded body parts -that have been used for trainees to 'practise' the manual and perceptual skills that are relevant to clinical work (Buck, 1991;Rosen, 2008). In contemporary settings for healthcare education, the use of physical, and often computer-based, simulators is prevalent and is designed to broaden the students' preclinical experience as well as to overcome concerns associated with practising on human subjects early in a student's apprenticeship.…”
Section: Introductionmentioning
confidence: 99%
“…Training for clinical practice, however, is not confined to work on the body of live humans. Indeed, there is a long and significant history of the use of 'simulators' in both medical and dental education -including the use of cadavers and discarded body parts -that have been used for trainees to 'practise' the manual and perceptual skills that are relevant to clinical work (Buck, 1991;Rosen, 2008). In contemporary settings for healthcare education, the use of physical, and often computer-based, simulators is prevalent and is designed to broaden the students' preclinical experience as well as to overcome concerns associated with practising on human subjects early in a student's apprenticeship.…”
Section: Introductionmentioning
confidence: 99%
“…Faria, (1998) for instance, revealed that 97.5% of business schools today use simulation games in their curricula. Medical simulations have been steadily replacing traditional skills teaching (Buck, 1991). Management students have found it effective to practice emergency response strategies without fear of negative personal or organizational consequences (Keith and Frese, 2008).…”
Section: An Exploratory Study On Simulated Teaching As Experienced By Education Studentsmentioning
confidence: 99%
“…There are reasons of cost, reluctance to adopting new methods of teaching and the skepticism that what was learned from a simulator may never be transferred to actual learning. A harder challenge to meet is the fact that simulations can never fully replicate real life experience and may even fail to include something essential in their systems (Buck, 1991;Bell, Kanar & Kozlowski, 2008;Greenberg & Eskew, 2009). However, recent policy recommendations for professional development promote the use of simulation models where exposure to the real environment may be impossible.…”
Section: Theories and Simulation Modelsmentioning
confidence: 99%
“…She was midwife in the court of King Louis XV and in the 1700s she created the "machine" i.e. simulators to train midwives in France (2). Her mannequins were very popular as they looked very realistic and could be used to learn how to manage normal childbirth and childbirth complications.…”
Section: Introductionmentioning
confidence: 99%